Characterizing a Production or a Cost Function by Elasticities of Substitution - Kang, H.; Brown, G. (Review of Economic Studies, 1980)
Heejoon Kang, Gardner Brown; Characterizing a Production or a Cost Function by Elasticities of Substitution, The Review of Economic Studies, Volume 47, Iss